Graphing statistic data : creating better chart - Wallgren,Anders; Wallgren,Britt; Persson, Rolf.; Jorner, Ulf.; Haaland, Jan-Aage. (New Delhi : Sage publication, 1996)
This book introduces the technique and art of producing good charts. Carefully written with many examples and illustrations, the book begins with an introduction to the building blocks of charts (axes, scales and patterns) and then describes each step involved in creating effective and easy-to-read charts.
Includes bibliography and index.
Keywords: Statistics -- Graphic methods; Statistique -- Méthodes graphiques